"MASAMO" Benih Lele Berkualitas dan Tahan Banting - Ro’uf, Muhammad Abdul; Mafkhuri, Taif; Fatmawati, Reni; Shofiatun, Shofiatun (Program Kreativitas Mahasiswa - Kewirausahaan, 2014)
National level catfish consumption in 2003 increased by 18.3%, from 24 991 tonnes / year to 57 740 tonnes / year. Meanwhile, demand for seed catfish also continue to increase from 156 million in 1999 to 360 million in 2003, an increase on average by 46% per year. Catfish seed needs until the end of 2013 was estimated at> 1.95 billion birds. Seeing the potential of spawning catfish business is very prospect for business on the run. However the quality of the parent catfish in Indonesia, which has been greatly reduced, making the longer cultivation time. Markets need a brand new brood. the longer service life. Whereas cultivated catfish remain the same means declining quality of seeds. in 1986 almost without introduction of a new strain in 15 years, except in 2004, a result Sangkuriang the longevity catfish cultivation, the more vulnerable to climate change, the stress level is high, then the lower feed efficiency. Catfish "MASAMO" is a latest types of African catfish was proved superior and quality, have a strong immune system can even live in extreme weather catfish may be new hope for the world catfish cultivation. However this type of catfish in use yet stout general, for the cultivation and catfish development this type should be mandatory to do to increase the productivity of the National catfish. Keywords : masamo seed quality